Politik Perampasan Tanah: Kematian Senyap Emansipasi dalam Hukum Agraria - Rofi Wahanisa; Syahwal -; Eko Mukminto (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2025)
In the midst of Indonesia's ongoing wave of development, agrarian conflicts that manifest in land grabbing have become increasingly prominent, despite frequently lacking clear legal justification. This study critically examines the role of law in facilitating and grabbing and interrogates the mechanism through which legal frameworks come to serve such a function. It addresses a significant gap in the scholarly discourse concerningthe legal dimensions of land dispossession. Employing a non-doctrinal approach, this research draws upon an extensive literature studies, regulatory analysis, and judicial decision reviews. The findings reveal that land grabbing in Indonesia is not merely driven by informal practices or extralegal coercion. Rather, it is frequently facilitated through legal instruments, most notably within the framework of National Strategic Projects (PSN). These projects demonstrate how the law is mobilized to legitimize dispossession, masking structural violence behind the veneer of legality. In this context, the emancipatory vision of Indonesian agrarian law faces systemic erosion. Rather than fading passively, it is actively dismantled under the influence of neoliberal imperatives embedded in post-1997 policy reforms. Ultimately, this study shows that law is not a neutral arbiter in agrarian conflict, but a powerful tool of accumulation by dispossession.